Correcta aplicación del esquema sancionatorio en la legislación aduanera por el ingreso ilegal de mercancías no declaradas. - Caraguay Asuncion, Jorge Luis (Machala : Universidad Técnica de Machala, 2022)
Ecuador, being bordered by Peru and Colombia, is a daily victim of different customs infractions such as receiving, fraud and smuggling, the latter being the most applied, in such a way that it harms the country's economy. For this reason, thanks to the National Customs Service of Ecuador (SENAE), which regulates and controls the entry and exit of goods, these irregularities can be controlled to the maximum, duly complying with the corresponding sanctions established in the COPCI and the COIP. This work was carried out with the objective of identifying the correct application of the sanctioning scheme in the customs legislation for the illegal entry of undeclared goods, through the exhaustive review of the Integral Penal Code (COIP) and the Organic Code of Production, Commerce and Investments (COPCI), established in Book V of Competitiveness and Customs Facilitation. For the solution of the case study, the qualitative approach was used through a documentary analysis, since scientific articles based on the research topic and legal sources were thoroughly reviewed. It was evidenced that the solution of the case was treated as a contravention with smuggling conduct and not as a crime, and the corresponding sanction was calculated according to what is stipulated in the COPCI in Art.- 191 Applicable Sanctions literal g) and finally it was determined that the owner of the merchandise should pay a fine of $ 2,910.31.
Ecuador al estar limitada con fronteras como Perú y Colombia, es víctima diaria de distintas infracciones aduaneras tales como receptación, defraudación y contrabando, este último es el más aplicado, de tal manera que perjudica la economía del país. Por ese motivo, gracias a el Servicio Nacional de Aduanas del Ecuador (SENAE), quién regula y controla el ingreso y salida de mercancías, se puede controlar al máximo estas irregularidades, cumpliendo debidamente con las sanciones correspondientes establecidas en el COPCI y el COIP. El presente trabajo se realizó con el objetivo de identificar la correcta aplicación del esquema sancionatorio en la legislación aduanera por el ingreso ilegal de mercancías no declaradas, mediante la revisión exhaustiva del Código Integral Penal (COIP) y el Código Orgánico de la Producción, Comercio e Inversiones (COPCI), establecido en el libro V de la Competitividad y de la Facilitación Aduanera. Para la solución del caso práctico se utilizó el enfoque cualitativo mediante un análisis documental, ya que se revisó minuciosamente artículos científicos basados en el tema de investigación y también de fuentes legales. Se evidenció que la solución del caso se trató de una contravención con conducta de contrabando y no como un delito, y la sanción correspondiente se calculó de acuerdo a lo estipulado en el COPCI en el Art.- 191 Sanciones Aplicables literal g) y finalmente se determinó que el dueño de la mercancía debía pagar una multa de $ 2.910,31.
Keywords: CONTRABANDO; CONTROL ADUANERO; CONTRAVENCIONES; COPCI